Economic redevelopment in bituminous coal : the special case of technological advance in United States coal mines, 1930-1960 - Christenson, Carroll Lawrence (Cambridge, Harvard University Press, 1962)
This book analysed the basic components of bituminous development in the United State since 1930
Includes bibliography.
asm: 21/01/19
Loans
Keywords: Coal mines and mining; Bituminous coal; Economic redevelopment